Biliary motility in health and disease - Luman, Widjaja (The University of Edinburgh, 1997)
This thesis examined several aspects of biliary physiology, the incidence of the post-cholecystectomy syndrome and changes in sphincter of Oddi (SO) motility following cholecystectomy.

Gallbladder emptying starts before the stomach begins to empty and before nutrients reach the small bowel to stimulate cholecystokinin (CCK) release. The mechanism of the early phase of gallbladder emptying is unclear. Gallbladder emptying was examined in a group of volunteers after ingestion of a fatty meal, a sham meal and gaseous gastric distension. The early phase of gallbladder emptying was found to be associated with CCK release. In most cases, gaseous gastric distension and sham feeding did not cause significant gallbladder emptying or CCK release but in a minority of individuals early gallbladder emptying followed sham feeding and this was associated with increased plasma CCK concentrations. Early release of CCK could be mediated by a combination of vagal-cholinergic stimulation and neuro-hormonal reflex in response to bombesin release by intragastric nutrients.

The effect of nitric oxide (NO) upon gallbladder motility was examined in a group of volunteers after fatty meal during infusion with NO donors (glyceryltrinitrate and sodium nitroprusside), normal saline and hydralazine as a hypotensive control agent. Postprandial gallbladder emptying was significantly reduced during infusion with the NO donors. This inhibitory effect was independent of hypotension and CCK release. This inhibitory effect of NO donors was also observed on isometric contraction of isolated gallbladder muscle strips.

The effect of NO on the SO was examined by topical infusion of glyceryltrinitrate to the ampulla during SO manometry. Basal tone and phasic activity were both suppressed. This finding may have therapeutic application for stone extraction and duct cannulation during endoscopic retrograde cholangiopancreatography.

Symptoms were assessed in 100 patients before and six months after laparoscopic cholecystectomy (LC) with standard questionnaire. 13% of patients had persistent biliary symptoms. Pre-operative abdominal bloating and consumption of antidepressant were found to be significantly more prevalent in these subjects compared to padents who had successful operations.

SO dysfunction is a cause of post-cholecystectomy pain. We hypothesised that LC could destroy cholecysto-sphincteric nerves leading to SO dysfunction. SO manometry was performed in a group of volunteers before and six months after LC. Following LC, the SO was not inhibited by CCK. This could lead to relative post-prandial biliary obstruction and result in post-cholecystectomy pain in susceptible individuals and to dilatation of the common bile duct.

Several issues and concepts arose from the work of this thesis. The mechanism underlying the early release of CCK needs further investigation. The clinical relevance of the effects of NO upon biliary tract motility remains to be explored. It is hoped that future research in this area will help to clarify these issues.